2017
DOI: 10.18488/journal.8.2017.54.457.464
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Feldstein-Horioka Puzzle in Transition Economies

Abstract: Article HistoryThe relationship between domestic savings and investments has become one of the most important issues discussed in economic theory with globalization of national financial markets. Is really domestic investment financed by global funds or domestic savings are still an important fund source for domestic investments? In this study, the relationship between savings and investments between years 1995 and 2014 is tested by panel data method in the transition economies (Czech Republic, Estonia, Hungar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In other words, this study concluded that the FH hypothesis is invalid in G20 countries. Because Feldstein and Horioka found a coefficient between 0,95 and 0,85 in their studies, it shows that the coefficient found is much lower than they estimated (Adıgüzel et al, 2017). The emergence of a more integrated world economy with the increase in economic freedom and the removal of barriers to goods, services, capital flows and international migration, that is, globalization (Bahtiyar and Yaglikara, 2022) is the most important reason for high capital mobility.…”
Section: Discussionmentioning
confidence: 95%
“…In other words, this study concluded that the FH hypothesis is invalid in G20 countries. Because Feldstein and Horioka found a coefficient between 0,95 and 0,85 in their studies, it shows that the coefficient found is much lower than they estimated (Adıgüzel et al, 2017). The emergence of a more integrated world economy with the increase in economic freedom and the removal of barriers to goods, services, capital flows and international migration, that is, globalization (Bahtiyar and Yaglikara, 2022) is the most important reason for high capital mobility.…”
Section: Discussionmentioning
confidence: 95%